Effective Methane Extraction Radius after High-Pressure Water Jet Slotting - Hu Ke; Xia Binwei; Liu Chengwei; Lu Yiyu (Geofluids)
The effective radius of methane extraction after high-pressure water jet slotting is the most important parameter for borehole optimization and extraction time planning. We applied a steady flow model and thermal-hydrological-mechanical (THM) coupling model to calculate the effective radius after high-pressure water jet slotting. Field measurements at the Zhongliangshan coal mine show that both the steady flow model and the THM coupling model can accurately represent the effective radius, and the THM coupling model provides further information regarding extraction time. After that, a variety of factors, including extraction time, coal burial depth, slot radius, initial permeability, and initial methane pressure, are discussed. The effective radius of a slotted borehole is 1.94 times larger than that of a conventional borehole.